Cortical Synchrony as a Mechanism of Collinear Facilitation and Suppression in Early Visual Cortex - Evers, Kris; Peters, Judith; Senden, Mario (Frontiers in Systems Neuroscience, 2021)
Stimulus-induced oscillations and synchrony among neuronal populations in visual cortex are well established phenomena. Their functional role in cognition are, however, not well understood. Recent studies have suggested that neural synchrony may underlie perceptual grouping as stimulus-frequency relationships and stimulus-dependent lateral connectivity profiles can determine the success or failure of synchronization among neuronal groups encoding different stimulus elements. We suggest that the same mechanism accounts for collinear facilitation and suppression effects where the detectability of a target Gabor stimulus is improved or diminished by the presence of collinear flanking Gabor stimuli. We propose a model of oscillators which represent three neuronal populations in visual cortex with distinct receptive fields reflecting the target and two flankers, respectively, and whose connectivity is determined by the collinearity of the presented Gabor stimuli. Our model simulations confirm that neuronal synchrony can indeed explain known collinear facilitation and suppression effects for attended and unattended stimuli.